What’s in the Mix? Mixed-Use Architecture in the Post-World War II Years and Beyond - Ben-Asher Gitler, Inbal (2022)
Mixed-use housing (MUH) has proliferated in recent years, largely in connection with high-rise mixed-use housing and large urban developments. Whereas housing architecture integrating additional functions has been designed throughout history, post-World War II architects proposed innovative ideas and designs for modern MUH. This article explores MUH of that period as an experiment that articulated urban hierarchies by integrating elements belonging to the different scales of the city into housing plans. I analyze the terminological frameworks proposed by Team 10 in Europe and Denise Scott Brown and Harvey Perloff in the United States, tracing how these evolved into groundbreaking designs that redefined the architecture of MUH. I demonstrate how architects negotiated terms such as “habitat,” which engaged community, as well as “human association” and “urban reidentification” in their practice. Thinking about these terms, I propose accessibility, participation, reuse, and diversity in formal design as elements from the recent past that can provide tools for rethinking present and future MUH.